Uncle Tungsten memories of a chemical boyhood - Sacks, Oliver W. 1933-2015 (Knopf, 2001)
Long before Oliver Sacks became a neurologist and one of our finest science writers, he was a small English boy fascinated by metals -- and also by chemical reactions, the louder and smellier the better. His curiosity was encouraged and abetted by brilliantly quirky relatives: Auntie Len, who taught him that the beauty of numbers can be found in the spiral face of a sunflower; Uncle Dave, who invited the boy to his light-bulb factory; and two older brothers who entertained him by making ammonium dichromate "volcanoes." But Sacks's childhood was interrupted by the outbreak of the Second World War, when he was evacuated from London and sent to live in a boarding school that rivaled Dickens's grimmest creations. He was sustained through those difficult years by his passion for learning and for finding patterns in the world around him. Overflowing with humor, sadness, sensuous recollection, and the almost physical rapture of discovery, Uncle Tungsten re-creates the wonder of science as it is first experienced and chronicles the birth of an extraordinary and original mind.
Keywords: Sacks, Oliver W - Enfance et jeunesse; Sacks, Oliver W - Et la chimie; Sacks, Oliver W; Sacks, Oliver W. -- 1933-2015; Chemie; METAIS; Natuurwetenschappen; QUÍMICOS (BIOGRAFIAS); TUNGSTÊNIO; Naturwissenschaft; Neurologists -- England -- Biography; Neurology -- Personal Narratives; Autobiografie; Biografie